INTRATESTICULAR INJECTION OF 20% HYPERTONIC SODIUM CHLORIDE AS A NOVEL CASTRATION METHOD: A PRECLINICAL STUDY - Hendry, Marta; Hardjowijoto, Sunaryo; Purnomo, Basuki B; Joewarini, Endang; Meles, Dewa Ketut; P, Widodo J (Indonesian Urological Association, 2010)
Objectives: To demonstrate that intratesticular injection of 20% hypertonic sodium chloride can result in permanent castration and to evaluate serum changes in sodium chloride levels. Materials and Methods: A total of 40 Wistar rats were divided into 4 groups, consisting of bilateral orchidectomy (n=10), control (n=10) and 2 groups receiving intratesticular injections of 20% sodium chloride (n=10 in each group). Serum testosterone was measured on day 0, day 1, day 15 and day 30. Serum sodium chloride was assessed before injection, at 1 hour and 24 hours after injection. All testicles were harvested for histological examination. One way ANOVA and student t-test were used for statistical analysis. Results: Serum testosterone decreased to castrate levels in the orchidectomy and injected groups with no significant difference (p>0,05). Significant rise in serum sodium chloride was found 1 hour post injection (p<0,05) but after 1 day it decreased significantly (p<0,05). There was no significant difference in histopathological findings between the 2 injected groups after day 15 and 30 (p>0,05). Conclusion: Twenty percent hypertonic chloride injection has the same permanent castration effect with bilateral orchidectomy in rats. The serum sodium chloride changes did not reach the lethal level for rats. Therefore this treatment has a promising potential as a novel and cost-effective castration method with the additional benefit of retaining both testes.